1980
DOI: 10.1159/000250482
|View full text |Cite
|
Sign up to set email alerts
|

Deficit of Cell-Mediated Immunity, Chromosomal Alterations and Defective DNA Repair in a Case of Dyskeratosis Congenita

Abstract: A case of dyskeratosis congenita with depressed responsiveness to policlonal mitogens (PHA, Con-A, PKM) and negative skin tests (PPD, SK-SD, Candidin, Trichophytin) is reported. Chromatid breaks and reduction of the capacity of DNA repair were also present. The findings are discussed in relationship to the prognosis of dyskeratosis congenita.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
2

Year Published

1984
1984
2006
2006

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 9 publications
2
4
0
2
Order By: Relevance
“…Although his CMV disease has been controlled with prolonged gancyclovir therapy, it has resulted in severe permanent visual impairment. Immune function studies in this patient prior to transplant showed a reduction in T-cell numbers, which has been previously described in association with opportunistic infections in individuals with dyskeratosis congenita (Giannetti & Seidenari, 1980;Connor & Teague, 1981;Weideman et al, 1984;Rose & Kern, 1992;Lee et al, 1992).…”
Section: Discussionsupporting
confidence: 75%
“…Although his CMV disease has been controlled with prolonged gancyclovir therapy, it has resulted in severe permanent visual impairment. Immune function studies in this patient prior to transplant showed a reduction in T-cell numbers, which has been previously described in association with opportunistic infections in individuals with dyskeratosis congenita (Giannetti & Seidenari, 1980;Connor & Teague, 1981;Weideman et al, 1984;Rose & Kern, 1992;Lee et al, 1992).…”
Section: Discussionsupporting
confidence: 75%
“…'2,16,20-23 That these alterations might also result in functional effects is suggested by the evidence of cutaneous anergy in 11 patients.5,10,12,19,23-28 and a reduced mitogenic response of the lymphocytes in 9 of the 15 patients. 10,11,21,23,26 Approximately 50% of the patients with an impaired lymphocyte response acquired recurrent infections or even opportunistic infections such as Pneumocystis carinii pneumonia (PCP). Defects in the complement system have not been described.…”
Section: Skin Alterationsmentioning
confidence: 99%
“…Several reports have documented a normal level of induced chromosomal instability in congenital dyskeratosis (reviewed in [10]; additional reports in [1,5]). In a few cases, an increase of the spontaneous breakage rate has been observed [3,8].…”
Section: Discussionmentioning
confidence: 99%